1999
DOI: 10.1016/s1350-4533(99)00074-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stimulus current pulse width on nerve fiber size recruitment patterns

Abstract: There have been theoretical studies presented that postulate a change in the stimulus current amplitude required to recruit nerve fibers with different stimulus current pulse widths. Based on these theoretical predictions, it has been suggested that the stimulus pulse width parameter may be used to selectively recruit fibers of different sizes and that this selectivity should increase with increasing distance from the stimulus electrode. In this paper, a simulation study of the recruitment patterns of a popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 17 publications
0
43
0
Order By: Relevance
“…It has been shown that at different stimulus pulse widths, the nerve fibers recruited by the stimuli were also different. 29 A typical example is that peripheral sensory fibers are more effectively evoked with longer pulse width than motor fibers. 30 Our fMRI data showed that the cS1 CBV response exhibited two phases during pulse-width modulation: in phase 1, the responses increased with pulse width and peaked B3 milliseconds.…”
Section: Neurovascular Responses In the Striatummentioning
confidence: 99%
“…It has been shown that at different stimulus pulse widths, the nerve fibers recruited by the stimuli were also different. 29 A typical example is that peripheral sensory fibers are more effectively evoked with longer pulse width than motor fibers. 30 Our fMRI data showed that the cS1 CBV response exhibited two phases during pulse-width modulation: in phase 1, the responses increased with pulse width and peaked B3 milliseconds.…”
Section: Neurovascular Responses In the Striatummentioning
confidence: 99%
“…Increasing the PA produces a stronger depolarising drive that travels deeper into the underlying tissue [23] and recruits a greater number of motor units, [16] whereas adjusting the PD influences not only the number of recruited motor units, but may also influence the selectivity of motor unit recruitment, due to threshold differences that exist between axons of different diameter lying at the same distance from the stimulating electrodes. [24][25][26] Thus, it may be possible to apply different combinations of PA and PD that generate contractions of equivalent torque, yet differing fatigue-resistance, through the activation of somewhat separate populations of motor units based on differences in the location, and threshold, of axons relative to the FES electrodes. With this in mind, the purpose of the present experiments was to determine whether optimal PA and PD combinations (i.e., optimal (PA,PD) pairs), those that minimize fatigue, differ for separate levels of generated torque.…”
Section: Introductionmentioning
confidence: 99%
“…Func tional electrical stimulation (FES) is a discipline where speci ficity associated with nerve fiber excitation and signal detection is highly desirable. One of the predominant issues related to the field-based approach in FES is the inability to specifically con trol excitation and isolate signal detection at the level of indi vidual nerve fibers [5].…”
Section: Introductionmentioning
confidence: 99%